Innovation cooperation in East Germany - only a half-way success? - Jutta Günther (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2003)
The paper focuses on the question whether enterprises that engage in innovation cooperation with external partners are more innovative and thus more productive than non-cooperating firms. A comparison between East and West Germany is being made. It shows that cooperating enterprises in East and West Germany are indeed more innovative than non-cooperating firms, but there remains a clear productivity gap between East and West German cooperating firms. Furthermore, in East Germany - different from West Germany - non-cooperating firms are even more productive than cooperating firms.
urn:nbn:de:gbv:3:2-20356
Keywords: 330; Forschungskooperation; Industrielle Forschung; Innovation; Unternehmenskooperation; Produktivität; Neue Bundesländer